Seeking to Be Heard: Reflections on the Value of a Partnership Approach to Involving Victims in the Development of Domestic Abuse Policy and Practice - Laura Hammond; Silvia Fraga Dominguez; Jenny Richards (Behavioral Sciences)
This paper outlines the development and delivery of a novel, collaborative, co-production approach to incorporating lived experience in the development of policy and practice in the area of domestic abuse. “SEEKERS” (Sharing Experience, Expertise and Knowledge for Effective Responses and Support) is an initiative which brings together victims and advocates, police, practitioners and researchers as equal partners. It creates opportunities for them to share their experiences, expertise, and knowledge, so that others can learn from these and use this learning in addressing domestic abuse-related issues more effectively. Throughout this paper, we discuss some of the challenges encountered in developing and delivering activities and how these were addressed. Notable benefits of the approach will be highlighted, as indicated by feedback from those involved in a range of capacities, including police and law enforcement practitioners, policy makers, councillors, service providers, support services, victim advocates and survivors of domestic abuse. It is hoped that this paper will contribute to ongoing discussions regarding the ways in which different agencies and stakeholders can work together more effectively and how we can create methods and spaces to support meaningful interaction, collaboration, and co-production with victims.